Augmenting Communicative Environments for People With Acquired Neurogenic Disorders: Exploring Situated Discourse Analysis. Issue 1 (January 2021) - Hengst, Julie A.; Sherrill, Martha H.
Abstract : This theoretical review article describes situated discourse analysis (SDA) and explores its implications for communication sciences and disorders. Drawing on situated theories of cognition and communication, SDA aims to understand real-time communicative processes of people engaging in complex sociocultural activities in specific sociomaterial environments . For SDA, discourse points first to the multimodal processes, not the products, of communicative interactions people engage in, and recognizes that these processes are fundamentally complex, distributed, and emergent. The article begins by defining SDA and describing four theoretical principles that guide this approach. We illustrate ways SDA might alter and advance theory, research, and clinical practice by considering its application to understanding the use of augmentative and alternative communication (AAC) technologies by adults with neurogenic communication disorders and their routine partners. We then explore empirical evidence from a methodologically diverse set of cases. The first considers Mialet's (2012) ethnographic study of Stephen Hawking and his use of AAC technologies, which highlights the complex, distributed, and emergent nature of situated discourse. We turn then to our clinical experiences, reflecting on what we have learned from our clients who have creatively repurposed technologies to remediate their activities and to mediate successful interactions and situated learning. Finally, we discuss a participatory design research project that used SDA as a guide for the innovative design of PIMs, pseudo-intelligent mediators (i.e., devices that sense the environment and act as active agents to mediate interactions). We conclude the article with a discussion of ways SDA contributes to and advances our research and clinical practice.